Impressions of the most comprehensive urban regeneration project implemented in Istanbul - Turgut, S. (WIT PRESS/COMPUTATIONAL MECHANICS PUBLICATIONS, 2009)
The urban regeneration efforts in the district of Kucukcekmece will be analyzed within the scope of the problems described. Kucukcekmece, one of the pioneer districts of Istanbul, has been trying a new and different regeneration process in Turkey. The settlement area, having quite significant potential within Istanbul as well as so many intensive and complicated problems, entered an active process in terms of planning and initiated efforts that could also serve as a locomotive for the planning efforts of Istanbul. However, institutional relations, disintegration of planning and weakening of coordination and organization processes, disconnection between stages and processes of planning, the new but problematic legal structure defined within the scope of legal revisions made within the scope of the process of joining EU and technical deficiencies create significant threats for the success of the system. Within the scope of the example that will be analyzed within this framework, the stages of planning and implementation, blockages and the factors threatening the system will be analyzed against the expectations of the city and especially of the district of Kucukcekmece. The opportunities and threats of planning and planning management will be analyzed; proposals and strategies will be discussed.
Keywords: urban regeneration; urban strategies; planning management; management of urban regeneration; Kucukcekmece regeneration projects; Architecture; Environmental Sciences & Ecology; Public Administration